INFRASTRUCTURE DEVELOPMENT AND INTRA-REGIONAL TRADE: THE CASE OF EAST AFRICAN COMMUNITY - Ochieng, James; Abala, Daniel; Mbithi, Mary (The European Journal of Applied Economics, 2020)
The study empirically established the relationship between infrastructure stock and bilateral trade in EAC for the period 1996 to 2018. Infrastructure augmented gravity model was estimated using total bilateral exports for the EAC Partner States. Infrastructure was disaggregated into transport and ICT infrastructures. Two institutional variables, control of corruption index and regulatory quality were incorporated in the model. By employing a random effects model, the results confirmed that both ICT and transport infrastructures positively impacts on the volumes of total bilateral exports in EAC. However, ICT infrastructure has a greater impact on trade flows compared to transport infrastructure. Therefore, more resources should be channelled towards increasing the stock of ICT infrastructure to propel regional integration in EAC.